Relationships between subjective ratings and objective measures of performance in speechreading sentences. - Demorest ME; Bernstein LE (Journal of Speech, Language & Hearing Research, 1997)
Ninety-six participants with normal hearing and 63 with severe-to-profound hearing impairment viewed 100 CID Sentences (Davis & Silverman, 1970) and 100 B-E Sentences (Bernstein & Eberhardt, 1986b). Objective measures included words correct, phonemes correct, and visual-phonetic distance between the stimulus and response. Subjective ratings were made on a 7-point confidence scale. Magnitude of validity coefficients ranged from .34 to .76 across materials, measures, and groups. Participants with hearing impairment had higher levels of objective performance, higher subjective ratings, and higher validity coefficients, although there were large individual differences. Regression analyses revealed that subjective ratings are predictable from stimulus length, response length, and objective performance. The ability of speechreaders to make valid performance evaluations was interpreted in terms of contemporary word recognition models.